The powers of speech : the politics of culture in the GDR - Bathrick, David, 1936-2020 1936-2020 (Modern German culture and literature, 1995)
In this definitive study, David Bathrick examines East German culture both before and after the fall of the Berlin Wall in November 1989. Bathrick argues that dissident East German writers were unique among East European literary intellectuals in that they attempted "to open up alternative spaces for public speech from within [the] framework" of Marxism and state socialism. Bathrick compares oppositional culture in East Germany to radical cultures elsewhere, examines the complex political and cultural relations of East and West Germany, traces the anguished history of the East German avant-garde, and describes the troubled effort to develop a revolutionary theatrical tradition in East Germany. The book also includes nuanced insights into the collapse of the East German political order in the late 1980s and more recent revelations about the collaboration of allegedly oppositional writers with the Stasi (state police).